HEPATOLITHIASIS - N. A. Brazhnikova; V. F. Tskhai; N. V. Merzlikin; M. E. Maryina; I. A. Lyzko; Ts. Ts. Zhambalov (Вестник хирургии имени И.И. Грекова, 2018)
The authors present an analysis of treatment results in 14 patients with hepatolithiasis. An influence of chronic opisthorchosis invasion on the frequency was determined. Hepatolithiasis was detected in 8 (0,14%) out of 5757 patients, who underwent the operation for cholelithiasis and its complications. The disease was found out in 6 (0,31%) patients out of 1965, who had cholelithiasis and accompanying chronic opisthorchosis. It was 2,2 times more frequent due to proliferative sclerotic changes of biliary system. The trasdermal teanshepatic cholangiography was contraindicated for opisthorchiasis injuries, because of the danger of subcapsular cholangioectates damage. The endoscopic retrograde cholangiopancreatography and the endopapillosphincterotomy were complicated due to extensive structures of the large duodenal papilla and distal section of the general bile duct. The patients were treated by using the cholecystectomy, extraction of stones from ducts, reconstruction of liver passage. Choledochoduodenostomy was performed with compulsory external drainage for ducts sanation from infections and helminthes in the case of the opisthorchiasis. Interportal infusions were carried out. The surgical, conservative and endoscopic treatment was required for multiple colangiolithiasis. The lethality consisted of 7,1%.